Topically Applied Luteolin /Quercetin-Capped Silver Nanoparticle Ointment as Antileishmanial Composite: Acceleration Wound Healing in BALB/c Mice. (7th February 2023) - Ebrahimzadeh, Azadeh; Karamian, Mehdi; Abedi, Farshid; Hanafi-Bojd, Mohammad Yahya; Ghatee, Mohammd Amin; Hemmati, Mina; Alemzadeh, Effat
Abstract : Cutaneous leishmaniasis is a major health problem in several parts of the world. However, existing drugs have various therapeutic effects on different Leishmania species and also cause many side effects. This study focuses on the use of the aqueous extract of quercetin in producing silver nanoparticles for the experimental treatment of cutaneous leishmaniasis in laboratory mice. Silver nanoparticles (AgNPs) were synthesized using quercetin and characterized by UV-Vis spectroscopy, DLS, FTIR, and FESEM. We investigated the antileishmanial activity of green synthesized AgNPs in vitro and in vivo . Synthesized AgNPs from quercetin macromolecules showed promising antileishmanial activity at an IC50 of 125 μ g/ml against promastigotes in vitro . In the in vivo study, L. major -infected BALB/c mice were treated topically with luteolin/quercetin-capped silver nanoparticle (AgNPQct) ointment for 21 consecutive days. As a result, this ointment reduced the inflammatory response compared to the untreated group (p < 0.05). The size of lesions in the luteolin/AgNPQct group showed a slight increase compared to other groups (p < 0.01). Biogenic silver nanoparticles along with the luteolin macromolecule can be an effective and reliable candidate for the design of antileishmanial drugs in the future.